Utilization of Toba Batak Traditional Culinary as Teaching Material for BIPA Learning Based on Local Wisdom - Manurung, Sophia Veronica; Sitompul, Candy Carobelli; Ritonga, Putri Luthfiyah; Situmorang, Anisah; Harahap, Safinatul Hasanah (Holistic Science, 2024)
This study aims to describe the utilization of traditional Toba Batak culinary as teaching material in learning Indonesian for Foreign Speakers (BIPA) based on local wisdom. The method used is descriptive qualitative with data collection through observation, in-depth interviews, documentation studies, and literature studies. The research subjects included BIPA teachers, BIPA participants, and sources related to traditional Toba Batak culinary. Data analysis was done inductively by reducing data, presenting data, and drawing conclusions. The results of the study describe the process of selecting and preparing BIPA teaching materials that integrate traditional Toba Batak culinary elements as a representation of local wisdom. The teaching materials include aspects of language, cultural knowledge, and language skills by utilizing the Toba Batak culinary context. This study reveals the challenges and strategies in presenting local wisdom in BIPA teaching materials as well as the perceptions of teachers and participants towards the use of traditional culinary-based teaching materials. The research findings can be a reference in developing BIPA teaching materials that are contextual, interesting, and provide an understanding of the richness of Indonesian culture, especially Toba Batak culture.